1994
DOI: 10.1111/j.1528-1157.1994.tb01797.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical Exercise in Women with Intractable Epilepsy

Abstract: Fifteen women with pharmacologically intractable epilepsy were given physical exercise (aerobic dancing with strength training and stretching) for 60 min, twice weekly, for 15 weeks. Seizure frequency was recorded by the patients for 3-7 months before the intervention, during the intervention period, and for 3 months after the intervention. Medication and other known seizure-influencing factors were kept as constant as possible. Self-reported seizure frequency was significantly reduced during the intervention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
116
0
9

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(132 citation statements)
references
References 31 publications
4
116
0
9
Order By: Relevance
“…we also might suggest that in refractory epilepsy, the possibility of exercise to provoke seizure could be increase. To reinforce the findings cited above, a study evaluating physical exercise in woman with intractable epilepsy showed a decreased the number of seizures during the aerobic physical training period 20 .…”
Section: Resultsmentioning
confidence: 94%
“…we also might suggest that in refractory epilepsy, the possibility of exercise to provoke seizure could be increase. To reinforce the findings cited above, a study evaluating physical exercise in woman with intractable epilepsy showed a decreased the number of seizures during the aerobic physical training period 20 .…”
Section: Resultsmentioning
confidence: 94%
“…Similarly, Nakken et al 9 observed that a 4-week exercise program improved the mental state and sociability of people with epilepsy. Furthermore, a regular exercise program improved performance and psychosocial quality of life of women with refractory epilepsy 10 . An improvement in the mood of individuals with epilepsy after 12 weeks of physical training has also been demonstrated by McAuley and collaborators 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of C and TLE groups on the Profile of Mood States (POMS) scores domains. activity is a non-pharmacological therapy which can provide health benefits such as reduction in the risk of cardiovascular and endocrine diseases, improvement in bone and muscle conditioning 25 , and prevention of psychological and emotional disturbances 10,15,17,26 . Consistent with this, mood disturbances are more prevalent among sedentary rather than physically active individuals 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of a teenage clinic, 207 patients (aged [11][12][13][14][15][16][17][18][19][20][21][22] were referred with "definite or probable epilepsy." 3 Epilepsy was the eventual diagnosis in 173 (84%).…”
Section: Review Of Diagnosismentioning
confidence: 99%